Fundamentals of astronomy. - Barbieri, Cesare, 1942-; Bertini, Ivano (Boca Raton : CRC Press, 2020)
Providing a broad overview of foundational concepts, this second edition of Fundamentals of Astronomy covers topics ranging from spherical astronomy to reference systems, and celestial mechanics to astronomical photometry and spectroscopy. It expounds arguments of classical astronomy that provided the foundation for modern astrometry, whilst presenting the latest results of the very-long-baseline interferometry (VLBI) radio technique, optical interferometers and satellites such as Hipparcos and GAIA, and recent resolutions of the IAU and IERS regarding precession, forced and free nutation, and Earth figure and rotation. Concepts of general relativity are explored, such as the advance of Mercury's perihelion, light deflection and black holes, in addition to the physical properties, orbits, and ephemerides of planets, comets and asteroids with an extension to visual binary stars orbital reconstruction. Extrasolar planets are also discussed, with reference to radial velocity and transits measurements by ground and space telescopes. Basic concepts of astronomical photometry, spectroscopy and polarimetry are given, including the influence of the terrestrial atmosphere. Classical works, such as Hipparchus, are mentioned in order to provide a flavor of the historical development of the field. It is an ideal textbook for undergraduate and graduate students studying astronomy, astrophysics, mathematics, and engineering. Supplementary and explanatory notes provide readers with references to additional material published in other literature and scientific journals, whilst solved and unsolved exercises allow students to review their understanding of the material. Features: Provides an introductory vision of arguments from spherical astronomy to celestial mechanics to astronomical photometry and spectroscopy Presents the information at an introductory level without sacrificing scientific rigor Fully updated throughout with the latest results in the field
Previous edition: 2007.
1. Spherical Astronomy. 2. First Notions on Astronomical Reference Systems. 3. Transformations of Coordinates. 4. First Notions on the Movements of the Earth and the Astronomical Times. 5. The Movements of the Fundamental Planes. 6.Dynamics of Earth's Rotation 7. Aberration of Light. 8. The Parallax. 9. Radial Velocities and Proper Motions. 10.The Astronomical Times the Atomic Time and the Earth Rotation Angle. 11.The Terrestrial Atmosphere. 12. The Two-Body Problem. 13. Orbital Elements and Ephemerides. 14. Elements of Perturbation Theories. 15. Eclipses, Occultations and Transits. 16. Elements of Astronomical Photometry. 17. Elements of Astronomical Spectroscopy.
OCLC-licensed vendor bibliographic record.
Keywords: Astronomy; SCIENCE / Astrophysics & Space Science